PERBEDAAN LAJU ALIRAN SALIVA TERSTIMULASI ANTARA PENGUNYAHAN PARAFIN WAX DENGAN PERMEN KARET XYLITOL PADA PASIEN TERINDIKASI GERD - Ridha Andayani; Sunnati .; Amatu Sholiha (Odonto : Dental Journal, 2016)
Background: Gastroesophageal Reflux Disease (GERD) is a condition of irreversibility (reflux) of stomach contents into the esophagus exceeds the normal amount and causes a variety of complaints. Reduction in salivary flow and decreased secretion of bicarbonate in the saliva cannot be avoided so that the patient is symptomatic GERD in the oral cavity in the form of halitosis and tooth erosion. Paraffin wax and chewing xylitol gum can be an alternative to increase the rate of saliva and neutralize the acid in patients with GERD. This study aimsto observes salivary flow rate differences between paraffin wax and xylitol gum patient - indicated GERD at RSUDZA in Banda Aceh.Method: This research is an analytic study with cross sectional approach and a subject of 17 people. Data were analyzed by statistical tests using Wilcoxon test.The results of this study, the salivary flows by chewing paraffin wax at the low category (52.9%), whereas salivary flows by chewing xylitol gum is the normal category (76.5%).Result: The data obtained P = 0.001 (P <0.05) for the difference between chewing paraffin wax and chewing xylitol gum.Conclusion: The conclusion from this study is a significant difference between salivary flows chewing paraffin wax and chewing xylitol gum in patient-indicated GERD at RSUDZA in Banda Aceh